Analisa Pengembangan Sentra Industri Kecil Menengah Arang Kayu Di Desa Ranggang, Ranggang Dalam Dan Batilai Kec. Takisung, Kab. Tanah Laut - Ridhoni, Miftahul; Achmad Priyadharma, Andi (Jurnal Administrasi Publik dan Pemerintahan, 2025)
Advanced industry can be realized through an independent industrial structure. Small and Medium Industries (SMEs) have a significant role in opening up employment opportunities. One of the SMEs that is developing in Takisung District is charcoal. This study identifies and analyzes the potential and problems, especially related to the business activities of SMEs Charcoal in Ranggang Village, Ranggang Dalam and Batilai, Takisung District, Tanah Laut Regency. The analysis carried out is potential analysis and financial feasibility analysis. Potential analysis is carried out by collecting data in the field, financial feasibility analysis is calculated using NPV and Payback Period. While for the preparation of strategies, SWOT analysis is carried out. This study concludes that in general the potential and financial feasibility of charcoal products are very profitable.